Liquid chromatography/mass spectrometry‐based plasma metabolic profiling study of escitalopram in subjects with major depressive disorder - Bandu, Raju; Lee, Hyun Jeong; Lee, Hyeong Min; Ha, Tae Hyon; Lee, Heon‐Jeong; Kim, Se Joo; Ha, Kyooseob; Kim, Kwang Pyo (Journal of mass spectrometry., 2018)
Liquid chromatography‐mass spectrometry (LC‐MS) method revealed the plasma metabolite profiles in major depressive disorder patients treated with escitalopram (ECTP) (n = 7). Depression severity was assessed according to the 17‐item Hamilton Depression Rating Scale. Metabolic profiles were derived from major depressive disorder subject blood samples collected after ECTP treatment. Blood plasma was separated and processed in order to effectively extract metabolites, which were then analyzed using LC‐MS. We identified 19 metabolites and elucidated their structures using LC‐tandem MS (LC‐MS/MS) combined with elemental compositions derived from accurate mass measurements. We further used online H/D exchange experiments to verify the structural elucidations of each metabolite. Identifying molecular metabolites may provide critical insights into the pharmacological and clinical effects of ECTP treatment and may also provide useful information informing the development of new antidepressant treatments. These detailed plasma metabolite analyses may also be used to identify optimal dose concentrations in psychopharmacotherapeutic treatment through drug monitoring, as well as forming the basis for response predictions in depressed subjects.